Devastating Lower Eyelid Squamous Cell Carcinoma in Patient with Xeroderma Pigmentosum - Novia Rahayu; Neni Anggraini; Rossalyn Sandra Andrisa (Majalah Oftalmologi Indonesia, 2016)
Background: Xeroderma pigmentosum (XP), an inherited condition of cellular sensitivity to ultraviolet (UV) radiation, mainly presents as cutaneous and ocular abnormalities, including neoplasia. This report aimed to demonstrate a devastating case of lower eyelid squamous cell carcinoma in XP patient.Case Illustration: Twenty four-year-old female with XP came with white plaque on both cornea. Excisional biopsy revealed a conjunctival intraepithelial neoplasia DD/ carcinoma in situ on right eye, and hyperplastic squamous epithelia on left eye. For nearly two years, she was lost to follow up, and revisited our clinic with a rapid growing, ulcerated, susceptible to bleed, red-yellowish mass, expanding to bulbar and tarsal conjunctiva, about 27 x 15 x 10 mm size, on her lower left eyelid, with restricted ocular movement. Incisional biopsy revealed a well-differentiated squamous cell carcinoma. In 6 weeks time, mass has grown to size 75 x 50 x 20 mm, and already infiltrated to superior eyelid and orbit.Conclusion: The nature of malignancy in XP patient is exceptionally progressive. Thorough education, close monitoring and early treatment is critical to prevent rapid deterioration and minimize possible impairment caused. Â Keywords: xeroderma pigmentosum, squamous cell carcinoma, eyelid squamous cell carcinoma, squamous cell carcinoma treatment